A genetic risk score is associated with statin-induced low-density lipoprotein cholesterol lowering. (April 2016) - Leusink, Maarten; Maitland-van der Zee, Anke H; Ding, Bo; Drenos, Fotios; van Iperen, Erik PA; Warren, Helen R; Caulfield, Mark J; Cupples, L Adrienne; Cushman, Mary; Hingorani, Aroon D; Hoogeveen, Ron C; Hovingh, G Kees; et al.
Aim: To find new genetic loci associated with statin response, and to investigate the association of a genetic risk score (GRS) with this outcome.Patients & methods: In a discovery meta-analysis (five studies, 1991 individuals), we investigated the effects of approximately 50000 single nucleotide polymorphisms on statin response, following up associations with p < 1 × 10 -4 (three independent studies, 5314 individuals). We further assessed the effect of a GRS based on SNPs in ABCG2, LPA and APOE .Results: No new SNPs were found associated with statin response. The GRS was associated with reduced statin response: 0.0394 mmol/l per allele (95% CI: 0.0171–0.0617, p = 5.37 × 10 -4 ).Conclusion: The GRS was associated with statin response, but the small effect size (˜2% of the average low-density lipoprotein cholesterol reduction) limits applicability.